Examining the relationship between social support and stress for parents of individuals with autism. (June 2020) - Robinson, Suzanne; Weiss, Jonathan A.
Highlights: In a multiple moderation model, perceived social support was associated with stress and received support was not. Child behaviour was consistently associated with parent stress. Although perceived support was correlated with stress, it did not act as a moderator or stress buffer. Abstract: Background: Social support has been considered a fundamental component of promoting parent and child well-being. Best understood as a multi-faceted resource, perceived and received support appear to be distinct concepts. The current study examined how received and perceived social support may be associated with, and moderate, the impact of child behavior problems on parent stress. Method: This study examined the stress-buffering effects of perceived and received support in a sample of 249 caregivers of individuals with autism. Results: Both types of support were significantly associated with less reported stress, when the two support types were examined individually. When considered together in a single model, received support was not uniquely associated with stress. Neither kinds of social support moderated the association between a commonly known stressors and stress. Conclusions: This was the first study involving parents of individuals with autism assessing the stress-buffering effects of social support using two types of support. Existing social support interventions typically focus on increasing received support as a mechanism for improving emotional well-being, and the current results suggest that perceived support may have a more robust and direct link.